Effects of prolactin and time delay on bone resorption: Mathematical modeling approach - Chontita Rattanakul (2018)
A mathematical model is developed in order to investigate the effect of prolactin on the mechanism of bone formation and resorption. By applying the singular perturbation technique to our model, we then obtain the explicit conditions on the system parameters which ensure the existence of limit cycle behavior corresponding to the oscillatory behavior observed in the clinical data. Numerical simulations are then carried out to support our theoretical analysis. In addition, we extend our model to investigate the effects of estrogen and parathyroid hormone supplements in patients with osteoporosis.